Infant formula with added Lacticaseibacillus rhamnosus GG supported adequate growth and was well tolerated in healthy term infants: a randomized controlled trial - Berseth, Carol Lynn; Yeiser, Michael; Harris, Cheryl L.; Kinnaman, Jennifer N.; Lappin, Victoria; Wampler, Jennifer L.; Zhuang, Weihong; Vanderhoof, Jon (Frontiers in Pediatrics, 2024)
Introduction Lacticaseibacillus rhamnosus GG (LGG) is a well-studied probiotic with a history of safe use. Methods In this double-blind, prospective study, growth and tolerance were evaluated in healthy term infants randomized to: marketed, routine intact cow's milk protein-based formula (Control, n = 172) or a similar investigational formula with added LGG (INV-LGG, n = 179; 106 CFU LGG®/g powder) from 14 to 120 days of age. Anthropometrics, stool characteristics, fussiness, and gassiness were evaluated through Day 120. Medically confirmed adverse events were recorded throughout the study period. The primary outcome was rate of weight gain from Day 14–120. Results Of 351 infants enrolled, 275 completed (Control, n = 131; INV-LGG, n = 144). No significant group differences in rate of weight gain from Day 14–120 were detected. Study formula acceptance and tolerance was good with no significant differences in study discontinuation due to study formula or parent-reported gassiness, stool frequency, or stool consistency; however mean fussiness relative to normal was significantly lower for INV-LGG vs Control at Days 60 and 90. Discussion In healthy term infants, a routine intact cow's milk protein-based formula with added LGG supported adequate growth and was well tolerated. Further studies are needed to evaluate potential benefits for fussiness and efficacy outcomes. Clinical Trial Registration Clinicaltrials.gov, identifier (NCT01897922).